Computational thinking as a heuristic endeavour: students’ solutions of coding problems 1 2 3 4 - Silva, Ricardo Scucuglia Rodrigues Da [UNESP]; Gadanidis, George; Hughes, Janette; Namukasa, Immaculate Kizito (UNICAMP - Faculdade de Educação, 2020)
In this paper we investigate students’ computational thinking in mathematics education. Specifically, through the analysis of teaching experiments conducted as qualitative case studies, we explore aspects of constructionism and problem solving. In different learning scenarios, pairs of elementary school and undergraduate students explored coding puzzles in order to complete a posed computational-mathematical task. From a constructionist point of view, the results indicate that the learning experience involved a problem solving spiral of description, execution, reflection and debugging. In the case of the experience of the undergraduate students, we also identified specific characteristics of computational thinking related to heuristic processes such as exploration, planning, analysis, and verification.

Neste artigo, investigamos o pensamento computacional de alunos em educação matemática. Especificamente, pela análise de experimentos de ensino conduzidos como estudos de caso qualitativos, exploramos aspectos do construcionismo e da resolução de problemas. Em diferentes cenários de aprendizagem, duplas de alunos do ensino fundamental e de graduação exploraram problemas de codificação para concluir uma tarefa matemático-computacional. Do ponto de vista construcionista, os resultados indicam que a experiência de aprendizagem envolveu uma espiral de descrição, execução, reflexão e depuração de problemas. No caso da experiência dos estudantes de graduação, também identificamos características específicas do pensamento computacional relacionadas a processos heurísticos, como exploração, planejamento, análise e verificação.
Pensamento Computacional como uma iniciativa heurística: soluções de estudantes sobre problemas de programação
Keywords: mathematics education; constructionism; problem solving; educação matemática; construcionismo; resolução de problemas